2005
DOI: 10.1029/2004jd005206
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous chemistry of individual mineral dust particles with nitric acid: A combined CCSEM/EDX, ESEM, and ICP‐MS study

Abstract: [1] The heterogeneous chemistry of individual dust particles from four authentic dust samples with gas phase nitric acid was investigated in this combined computer-controlled scanning electron microscopy with energy-dispersive X-ray (CCSEM/EDX) analysis, environmental scanning electron microscopy (ESEM), and inductively coupled plasma mass spectrometry (ICP-MS) study. Morphology and compositional changes of individual particles as they react with nitric acid were observed using conventional scanning electron m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
146
1

Year Published

2005
2005
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 167 publications
(157 citation statements)
references
References 45 publications
10
146
1
Order By: Relevance
“…Alpert and Ganor (2001) reported high carbonate content (29% CaCO 3 , 26% CaMg(CO 3 ) 2 ) for non-clay minerals sampled in Israel that appeared to originate from Algeria, Libya, and Israel. Laskin et al (2005) found little carbonate in Saharan and inland Saudi Arabian soil, but significant carbonate in soil from coastal Saudi Arabia and China. Given the regional differences in carbonate content, we consider a range of compositions.…”
Section: Dust Compositionmentioning
confidence: 99%
See 1 more Smart Citation
“…Alpert and Ganor (2001) reported high carbonate content (29% CaCO 3 , 26% CaMg(CO 3 ) 2 ) for non-clay minerals sampled in Israel that appeared to originate from Algeria, Libya, and Israel. Laskin et al (2005) found little carbonate in Saharan and inland Saudi Arabian soil, but significant carbonate in soil from coastal Saudi Arabia and China. Given the regional differences in carbonate content, we consider a range of compositions.…”
Section: Dust Compositionmentioning
confidence: 99%
“…During transport, CaCO 3 in dust can react with gases such as HNO 3 and SO 2 to form components that may enhance dust's ability to serve as CCN. The main product of the HNO 3 reaction is calcium nitrate, which deliquesces at low RH and greatly enhances dust 8/21/2006 hygroscopicity (Laskin et al, 2005). In the case of the SO 2 reaction with CaCO 3 , calcium sulfite appears to form, and the sulfite can be oxidized to sulfate by gas-phase ozone (Usher et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…For these particles, solubilizing reactions, such as uptake of nitric acid, may occur at the particle surface, and subsequent water exposure creates conditions ripe for reaction between OxA and di-valent cations (Laskin et al, 2012). Surface reactions between oxalic acid and metal chlorides can produce highly volatile hydrochloric acid, and evaporation of HCl will drive the in-particle equilibrium towards formation of the insoluble M-Ox complex (Laskin et al, 2005). Loss of volatile products occurs at the particle surface, leading to enrichment of the remaining lower volatility material at the particle surface.…”
Section: G Drozd Et Al: Inorganic Salts Interact With Organic Di-acidsmentioning
confidence: 99%
“…[17] Krueger et al [2004] and Laskin et al [2005a] experimented on authentic dust in a laboratory and demonstrated that calcites (CaCO 3 ) can react with gaseous HNO 3 to form Ca(NO 3 ) 2 , which can then deliquesce even under conditions as dry as RH < 12%. Ca-rich spherical particles found frequently in the Beijing atmosphere might well be the modified product of carbonate formed in this manner.…”
Section: Spherical Mineral Dustmentioning
confidence: 99%